Pancreatic Tail Schwannoma in a 44-Year-Old Male: A Case Report and Literature Review - Ahmed Abu-Zaid; Ayman Azzam; Hussam Abou Al-Shaar; Abdullah M. Alshammari; Tarek Amin; Shamayel Mohammed (Case Reports in Oncological Medicine)
Pancreatic schwannomas are exceedingly uncommon neoplasms. According to a recent study in 2012, less than 50 cases of pancreatic schwannoma have been described in the English literature over the past thirty years. The vast majority of pancreatic schwannomas take place in the head and body of pancreas, respectively. Herein, we report the case of pancreatic tail ancient schwannoma in a 44-year-old man who presented with a 4-month history of epigastric pain. On physical examination, epigastric region was moderately tender to palpation without evidence of a palpable mass. All laboratory tests were normal. Contrast-enhanced computed tomography (CT) scan showed a 9.2 × 9.5 × 11.5 cm, huge, and well-defined left suprarenal mass arising either from adrenal gland, pancreas, or retroperitoneum. The mass demonstrated mild heterogeneous enhancement with central cystic/necrotic area. No evidence of distant metastasis was identified. At laparoscopy, the mass was noticed to originate from pancreatic tail. Patient underwent surgical resection of pancreatic tail. Microscopic and immunohistochemical examination of the pancreatic tail specimen showed ancient schwannoma. Patient received no adjuvant therapy. At a postoperative 6-month followup, patient was completely asymptomatic and CT scan imaging showed no evidence of tumor recurrence. Moreover, a literature review on pancreatic schwannomas is presented.